2004
DOI: 10.1007/s00787-004-0380-4
|View full text |Cite
|
Sign up to set email alerts
|

Profiles, co-morbidity and their relationship to treatment of 191 children with AD/HD and their families

Abstract: Protocols in clinics are useful as this should maintain good practice and allow on-going monitoring, but they need precise use. Also, as many children with AD/HD present with co-morbid psychopathology and complicated family dynamics to Child and Adolescent Mental Health Services, this will influence assessment and treatment needs and require increased resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 28 publications
2
15
1
Order By: Relevance
“…In particular, maladaptive coping was significantly increased in the clinical group. These results are in agreement with previous research supporting an impaired emotional regulation among children with ADHD (Berlin et al, 2004;Braaten & Rosén, 2000;Thompson et al, 2004;Wheeler Maedgen & Carlson, 2000). However, the impaired adaptive coping found in Study 1 could not be replicated.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In particular, maladaptive coping was significantly increased in the clinical group. These results are in agreement with previous research supporting an impaired emotional regulation among children with ADHD (Berlin et al, 2004;Braaten & Rosén, 2000;Thompson et al, 2004;Wheeler Maedgen & Carlson, 2000). However, the impaired adaptive coping found in Study 1 could not be replicated.…”
Section: Discussionsupporting
confidence: 92%
“…A study by Whalen, Jamner, Henker, Delfino, and Lozano (2002) supports an emotional deficit among adolescents with severe symptomatology, showing more negative and fewer positive moods as well as lower alertness. Additional studies suggest an impaired psychosocial functioning, indicated by impaired self-esteem as well as a decreased school-and social-related quality of life compared to healthy controls, physically disabled children, and individuals with other psychiatric disorders (Bastiaansen, Koot, Bongers, Varni, & Verhulst, 2004a;Bastiaansen, Koot, Ferdinand, & Verhulst, 2004b;Escobar et al, 2005;Klassen, Miller, & Fine, 2004;Sawyer et al, 2002;Thompson et al, 2004;Topolski et al, 2004).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…More than 80% of children and adults with ADHD are likely to have at least one other psychiatric disorder and more than 50% are likely to have two [8,13]. Thus, ADHD is associated more often with at least one comorbid disorder than without any [14]. ADHD is associated with numerous developmental, cognitive, emotional, social, and academic impairments as well as various health risks that can significantly affect the academic performance of adolescents [8,13,15] and their parents' personal time [16][17][18].…”
mentioning
confidence: 99%
“…At its core, is a persistent and pervasive pattern of inattention and/or hyperactivity and impulsiveness. It often overlaps with other conditions (e.g., oppositional defiant disorder, conduct disorder, anxiety, and reading problems [2,3] and causes significant impairment across multiple functional domains [4]. Children with ADHD are more likely to fail at school and to go on to be unemployed [5,6], to be involved in crime [7], to use illegal substances [1] and to suffer from other comorbid mental health problems [8].…”
Section: Introductionmentioning
confidence: 99%